Post-COVID-19 Student and Faculty Perceptions of Online Computing Labs: Better Targeted, Better Perceptions, but Still Need Improvement - Yunfei Hou; Miranda May McIntyre; Joyce Fu; Jesus Herrera; Hani Aldirawi; Montgomery Van Wart (Education Sciences)
In many disciplines, the growth of online courses was propelled by the COVID-19 pandemic, but this trend moderated as health concerns receded. Before the pandemic, computer science-related disciplines were less keen on online labs because of their inherently hands-on nature. This study presents a comparative analysis of student and faculty perceptions towards online labs in three computing-related disciplines a year after the pandemic. Through a survey with 242 students and 20 faculty responses, we found students were, overall, positive about their online lab experience—as were faculty. Students and instructors both agree that (1) where provided, online lab courses are being taught effectively, and (2) it is crucial to continue investing in technology infrastructure to enhance the quality and accessibility of both online and in-person labs. However, students and instructors disagree on two issues: (1) teamwork for lab activities and assignments (i.e., faculty tended to have a more optimistic view of online collaborative activities); and (2) modality for lab sessions (i.e., student preferences were evenly split between synchronous and asynchronous labs while faculty mostly preferred synchronous online labs). Faculty appear more optimistic about the effectiveness of online labs but show heightened concern regarding technological disruptions. Notably, all comments from students asserted the importance of having recorded demonstrations, even when a live synchronous demonstration may have been provided. Utilizing recordings and making them available is an example of a best practice worth promoting despite the added effort for faculty.